The Indonesian National Defense and Economic Challenges and the Policies Needed: TANTANGAN PERTAHANAN DAN EKONOMI INDONESIA SERTA KEBIJAKAN YANG PERLU DILAKUKAN - Kennedy, Posma Sariguna Johnson (Fundamental Management Journal, 2017)
The future challenge for Indonesia's defense is the lack of defense budgets while defense issues will become more complex. This literature review would like to see the challenges of Indonesia ahead and the recommendations given to deal with it. The very limited natural resources causing future conflicts will be greatly influenced by the motivation of controlling resources through military force. To face it, the increasing quantity and quality of defense equipment must be considered by following the technology of today. Human resource development in quantity and quality must also be continuously carried out, such as with the training, education and absorption of the latest defense technologies. In addition, it is time for Indonesia's defense industry to be empowered in meeting the needs of national defense.